A people and a nation: a history of the united states - Norton, Mary Beth (Houghton Mifflin College Div Boston, 1989)
A People and a Nation is a spirited narrative that challenges students to think about the meaning of American history. Its thoughtful inclusion of the lives of everyday people, cultural diversity, work, and popular culture preserves the text's basic approach to American history as a story of all the American people. The end-of-chapter "Legacies for a People and a Nation" feature focuses on a specific event, movement, or fact covered in the chapter that shows a striking relevance to present-day events and controversies. The feature demonstrates how important the past is to the present and provides a forum for contemporary analysis. The "How Do Historians Know" feature demonstrates the process by which various pieces of historical evidence are used to reach conclusions about the past.